Eoarchean within-plate basalts from southwest Greenland: COMMENT - Szilas, Kristoffer; Hoffmann, J. Elis; Münker, Carsten; Dziggel, Annika; Rosing, Minik T. (Geological Society of America, 2014)
Jenner et al. (2013) reported the occurrence of, what they interpret as, Earth’s oldest ocean island basalts (OIBs) on the island of Innersuartuut, southwest Greenland. However, this interpretation hinges critically on the incompatible trace element contents of the presented rocks. Compared to Phanerozoic OIBs, the data of Jenner et al. exhibit lower Nb/La and Gd/Yb ratios, have negative Zr-Hf anomalies, and very low U and Th abundances. Thus, the highly incompatible trace elements are depleted relative to Hawaiian OIB and the compositions are completely different from HIMU- (high μ), EM1- (enriched mantle 1), and EM2-type OIB (see Hofmann, 2003).